ETNOBOTANI DI KEBUN TEMBAWANG SUKU DAYAK IBAN, DESA SUNGAI MAWANG, KALIMANTAN BARAT - Pradityo, Teguh; Santoso, Nyoto; Zuhud, Ervizal A. M. (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Iban or Dayak Iban is one of many tribes who live in some places of West Kalimantan province, one of them is in Sungai Mawang Village, Puring Kencana Districts, Kapuas Hulu District, West Kalimantan Province. As well as many tribes who still depend their lives on nature, Iban has many various local wisdoms in using surrounding nature. The example of land use patterns was tembawang (Kalimantan’s unique of agroforestry) as a place for food sources, medicines, building materials, complementary ceremony goods and other uses. This research aimed to identify useful plants species and its classification based on usefulness group and part of useful plants that used by local people of Sungai Mawang village from tembawang that they have. Data collection methods used were interviews and direct observations which were then analyzed by qualitative description. Based on etnobotany research conducted in 15 tembawang in Sungai Mawang Village, there were 122 plants, 97 genera and belong to 60 families which are used directly. The plants utilization can be classified into 63 species as food sources, 13 of them as ingredients & spices, 61 species as medicines, 32 as building material, 29 species for other uses, 9 as firewood and 4 species as ritual needs. Keywords: Dayak Iban, etnobotany, tembawang, useful plants